Somatotopic organization of ferret thalamus - Vázquez-García, Mario; Wallman, Marie-Josée; Timofeev, Igor (Frontiers in Integrative Neuroscience, 2014)
The stereotaxic reference marks of ferret skull have large variability and the reference point for stereotaxic experiments in ferret brain is difficult to define. Here, using extracellular single-unit recordings, we studied the somatotopic organization of cutaneous receptive fields in the ventroposterior medial (VPM) and the ventral posterolateral (VPL) nuclei of the ferret thalamus. The mechanical stimulation of the skin was done through air puffs. The skull was positioned according to Horsley-Clarke coordinate system. Most of the neurons responding to face skin stimulation were located +7 - +9 mm anterior, 2 – 3.9 mm lateral and 7-9.6 mm from cortical surface, whereas those responding to body skin stimulation were located +7 - +10 mm anterior, 3.3 - 5.5 mm lateral and 6.7 -10 mm from cortical surface. Out of 90 thalamic neurons recorded in this study, 58 responded to the body and the other neurons to the face stimulation. All neurons responded with spikes to stimulus onset, 37 % of neurons responded only to stimuli onset and offset and 22 % neurons fired tonically throughout stimulating epoch. The whiskers representation was located in the middle of the VPM nucleus, whereas those of the tongue, nose, bridge of the nose, supraorbital areas, upper and lower lips, and lower jaw were surrounding the whiskers representation. Within the VPL nucleus there was a clear topological correspondence from forelimb to hindlimb in the medial-to-lateral direction. Our findings indicate the whiskers representation in VPM or the forelimb-hindlimb representation in the VPL nucleus can be considered as a reliable reference in the ferret thalamus.